Over-expression of HSP70 attenuates caspase-dependent and caspase independent pathways and inhibits neuronal apoptosis - Sabirzhanov, Boris (2012)
HSP70 is a member of the family of heat-shock proteins that are known to be up-regulated in neurons following injury and/ or stress. HSP70 over-expression has been linked to neuroprotection in multiple models, including neurodegenerative disorders. In contrast, less is known about the neuroprotective effects of HSP70 in neuronal apoptosis and with regard to modulation of programmed cell death (PCD) mechanisms in neurons. We examined the effects of HSP70 over-expression by transfection with HSP70-expression plasmids in primary cortical neurons and the SH-SY5Y neuronal cell line using four independent models of apoptosis: etoposide, staurosporine, C2-ceramide, and β-Amyloid. In these apoptotic models, neurons transfected with the HSP70 construct showed significantly reduced induction of nuclear apoptotic markers and/or cell death. Furthermore, we demonstrated that HSP70 binds and potentially inactivates Apoptotic protease-activating factor 1, as well as apoptosis-inducing factor, key molecules involved in development of caspase-dependent and caspase-independent PCD, respectively. Markers of caspase-dependent PCD, including active caspase-3, caspase-9, and cleaved PARP were attenuated in neurons over-expressing HSP70. These data indicate that HSP70 protects against neuronal apoptosis and suggest that these effects reflect, at least in part, to inhibition of both caspase-dependent and caspase-independent PCD pathways.